Basin redox and primary productivity within the Mesoproterozoic Roper Seaway - Cox, Grant; Jarrett, A.; Edwards, D.; Crockford, P.; Halverson, G.; Collins, A.; Poirier, A.; Li, Zheng-Xiang (Elsevier Science BV, 2016)
The ca. 1.4 Ga Roper Group of the greater McArthur Basin in northern Australia comprises the sedimentary fill of one of the most extensive Precambrian hydrocarbon-bearing basins preserved in the geological record. It is interpreted to have been deposited in a large epeiric sea known as the Roper Seaway. Trace element data suggest that the redox structure of the basin was a shallow oxic layer overlying deeper suboxic to anoxic waters along with a prominent episode of euxinia. These anoxic and sulfidic conditions, as inferred by Mo, V, and U concentrations (molybdenum, vanadium and uranium), developed due to high organic carbon loading consistent with models that suggest that euxinic conditions cannot develop until the flux of organic matter is significantly greater than the flux of bioavailable iron, which permits sulphate reduction to proceed. Considering the high reactive iron and molybdenum contents of these shales and the requirement for S/Fe ratios > 2 for euxinia to develop, suggests that sufficient atmospheric O2 was available for oxidative scavenging of S and Mo from the continents. This is further supported by prominent negative cerium anomalies within these shales, indicative of active oxidative redox cycling of cerium. We propose that the high organic matter flux was the result of increased nutrient loading to the Roper Seaway from weathering of the continental hinterland. Data from both major and high-field strength elements (niobium, tantalum, zirconium and, hafnium) together with neodymium isotopes (143Nd/144Nd) indicate that a likely mechanism for this enhanced nutrient delivery was a shift in sedimentary provenance to a more primitive (i.e. mafic) precursor lithology. This switch in provenance would have increased phosphorus delivery to the Roper Seaway, contributing to high primary productivity and the onset of euxinia. This dataset and model serve as a basis for understanding the temporal evolution of the deepest sections of the Roper Seaway and finer scale changes in the environment at this time.